PENGARUH PAHAT ENDMILL NORMAL DAN VARIABEL HELIX ANGLE PADA METODE POCKET ZIG-ZAG TERHADAP CHATTER - Venusa Abriandika; Achmad As’ad Sonief; Yudy Surya Irawan (Jurnal Rekayasa Mesin, 2023)
The manufacturing industry mostly uses CNC Milling machines in processing products that require high precision values. This machine is capable of a wide variety of feeding methods, inclinations, feed speeds, various tool styles, and much more. The purpose of this research is to analyze one method of infeed direction with the Zig-Zag effect by using 2 types of normal and variable tool types combined with variations in spindle speed and DOC to find out which variable is effective and produce a smoother comparison of surface roughness values. The type of material tested was SS 304 because this material has good advantages against corrosion. From the results of research conducted on this material for the use of a variable tool, it has an average roughness value of 0.327 µm and for the results of the roughness test on the use of a normal tool, it has an average roughness value of 0.470 µm. From the results of this research, it can be concluded that the value of the Depth Of Cut (DOC), the roughness value are directly proportional, and the faster the spindle rotation, the frictional force generated also increases. The highest Ra value from the research results occurred in DOC 1.6 mm with a spindle speed of 2750 rpm using a variable tool of 0.361 µm and a roughness value of 0.516 µm on a normal tool. The conclusion of this research is that the variable tool produces a lower Ra value than the normal tool so that the type of material defects caused by chatter vibration can be reduced.